Definition of mutations in polyautoimmunity (2016)
Objectives Familial autoimmunity and polyautoimmunity represent extreme phenotypes ideal for identifying major genomic variants contributing to autoimmunity. Whole exome sequencing (WES) and linkage analysis are well suited for this purpose due to its strong resolution upon familial segregation patterns of functional protein coding and splice variants. The primary objective of this study was to identify potentially autoimmune causative variants using WES data from extreme pedigrees segregating polyautoimmunity phenotypes. Methods DNA of 47 individuals across 10 extreme pedigrees, ascertained from probands affected with polyautoimmunity and familial autoimmunity, were selected for WES. Variant calls were obtained through Genome Analysis Toolkit. Filtration and prioritization framework to identify mutation(s) were applied, and later implemented for genetic linkage analysis. Sanger sequencing corroborated variants with significant linkage. Results Novel and mostly rare variants harbored in SRA1, MLL4, ABCB8, DHX34 and PLAUR showed significant linkage (LOD scores are >3.0). The strongest signal was in SRA1, with a LOD score of 5.48. Network analyses indicated that SRA1, PLAUR and ABCB8 contribute to regulation of apoptotic processes. Conclusions Novel and rare variants in genetic linkage with polyautoimmunity were identified throughout WES. Genes harboring these variants might be major players of autoimmunity. © 2016 Elsevier Ltd